Application of Theory Reasoned Action In Intention to Use Islamic Banking In Indonesia - Reni, Andi; Ahmad, Nor Hayati (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
This paper investigates the constructs of Theoryof Reasoned Action (TRA), and Theory of Planned Behavior (TPB) (attitude,subjective norm, religion, knowledge, pricing, and government support) oncustomer behavioral intention and Islamic banking selection. This research usingPartial Least Square Structural Equation Modeling with variables such as:attitude, subject norm, religion, knowledge and government support, and pricing.The result shows that attitude, subject norm, religion, knowledge and governmentsupport are statistically significant effect on intention to select Islamic bank inIndonesia. Pricing however is not significant. The results imply that IndonesianIslamic banks should strategize ways to develop positive attitude and referenceamongst their customers through greater dissemination of knowledge about Islamicbanking while emphasizing on the religious compliance.DOI: 10.15408/aiq.v8i1.2513